High-efficient, spherical and thermal-stable carbon dots@silica fluorescent composite as rare earth-free phosphors for white LED. Issue 10 (July 2020) - Zhang, Xinguo; Sun, Zishan; Zhu, Zhenpng; Luo, Jiabao; Wu, Zhanchao; Wang, Zhengliang
Abstract: This paper reported a facile synthesis path to realize high-luminescent rare-earth-free composite powder, by embedding blue/green-emitting N-doped carbon dots into silica nano-spheres (CD@SiO2 ). Carbon dots were evenly dispersed in CD@SiO2 composites and eventually the aggregation-induced luminescence quenching is eliminated. Compared to the naked CDs, CD@SiO2 composites exhibit perfectly spherical morphology with average size of ~200 nm, significantly enhanced emission intensity (>4 times) and better thermal stability ( T 50  > 150 °C). As-synthesized CD@SiO2 own strong blue/green emission with high quantum efficiency (QE) over 60%. White LEDs prototypes with promising properties, i.e. CRI = 89.1, CCT = 4850 K and CIE coordinates = (0.3514, 0.3715), were fabricated by combining blue/green CD@SiO2 and red CdTe@CaCO3 composites with NUV chip. All results indicate that these rare-earth-free, mono-dispersed spherical, and thermal-stable composite materials with efficient blue/green emission could be an exceptional choice as phosphors for LED application.